Analysis of Knowledge, Attitude, and Environmental Support Factors on Clean and Healthy Living Behavior (PHBS) Among Students of STIKes Widya Dharma Husada Tangerang - Irviana, Fitriyati (Jurnal Kesehatan dan Kedokteran, 2025)
This study explores the influence of knowledge, attitude, and environmental support on Clean and Healthy Living Behavior (PHBS) among students of STIKes Widya Dharma Husada Tangerang. As a preventive health strategy, PHBS plays a crucial role in shaping student awareness and promoting well-being within academic settings. Utilizing a quantitative approach with a survey method, the research examines how each factor contributes both individually and collectively to behavioral outcomes. The results indicate that knowledge, attitude, and environmental support significantly affect students' engagement in PHBS. Among these, attitude emerges as the most influential determinant. The study underscores the need for continuous health education, positive attitude formation, and an enabling environment on campus to foster sustainable healthy living behaviors. These findings highlight the importance of integrated health promotion strategies in higher education institutions. Future research is encouraged to incorporate additional factors such as personal motivation and digital media influence in the context of health behavior change